2017
DOI: 10.3390/nu9121339
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Anthropometric Indicators to Monitor the Response to Treatment for Severe Acute Malnutrition in Rural Southern Ethiopia—Empirical Evidence

Abstract: The World Health Organization (WHO) recommends the assessment of nutritional recovery using the same anthropometric indicator that was used to diagnose severe acute malnutrition (SAM) in children. However, related empirical evidence from low-income countries is lacking. Non-oedematous children (n = 661) aged 6–59 months admitted to a community-based outpatient therapeutic program for SAM in rural southern Ethiopia were studied. The response to treatment in children admitted to the program based on the mid-uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
4
6
1
Order By: Relevance
“…Overall, this trial showed low rehabilitation from acute malnutrition in the outpatient treatment, in the standard as well as the experimental group. The weight gain in this trial was unfavorable to those reported by other CMAM programs where the average weight gains for children managed for acute malnutrition varied from 1.8 to 6.8 g/kg/day [ 42 , 46 , 60 , 61 , 62 ], and other studies in hospitalized children for treatment of SAM also found considerable higher rates of weight gain [ 7 , 9 ]. The lower weight gain in this trial could be caused by multiple factors, including the difference in adherence to an ideal management of patients with SAM, low daily feeding frequency, sharing, low acceptability and therefore a low overall consumption of RUTF.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Overall, this trial showed low rehabilitation from acute malnutrition in the outpatient treatment, in the standard as well as the experimental group. The weight gain in this trial was unfavorable to those reported by other CMAM programs where the average weight gains for children managed for acute malnutrition varied from 1.8 to 6.8 g/kg/day [ 42 , 46 , 60 , 61 , 62 ], and other studies in hospitalized children for treatment of SAM also found considerable higher rates of weight gain [ 7 , 9 ]. The lower weight gain in this trial could be caused by multiple factors, including the difference in adherence to an ideal management of patients with SAM, low daily feeding frequency, sharing, low acceptability and therefore a low overall consumption of RUTF.…”
Section: Discussioncontrasting
confidence: 93%
“…Some studies used weight gain either as g/kg/day [ 7 ] or weight gain percentage [ 33 ]. Others used recovery [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], 100% of mean WHZ of the population [ 41 ], or combinations of two indicators, for example weight gain (g/kg/day) and recovery [ 42 , 43 , 44 ], weight gain and mortality [ 45 ], MUAC and weight gain [ 46 ] or more than two indicators [ 47 , 48 , 49 ]. Nutritional programs using MUAC recommended a weight gain of 15–20% [ 2 ], to avoid non-applicability of WHZ for children admitted based on MUAC who already fulfilled the WHZ discharge criteria at admission and to avoid using height measurements [ 2 , 27 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies on the edema showed that dietary treatment improved edema even before the albumin concentration rose. Among edematous children, there was low plasma zinc concentration and which was strongly associated with nutritional edema and there were significant relationships between plasma zinc concentrations and stunting, skin ulceration, and wasting [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, children with SAM are admitted to health posts using MUAC < 11.5cm and get treated with ready to use therapeutic food and other treatments indicated in the protocol for a period of 8 weeks (Refer to the national SAM Guideline). Children with the lowest MUAC at admission showed a significant gain in MUAC but not weight, and children with the lowest weight-for-height/length (WHZ) showed a significant gain in weight but not MUAC and response to treatment was largest for children with the lowest anthropometric status at admission in either measurement modality by WHZ or MUAC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children with the lowest WHZ (WHZ < −3) showed a significant change on the average weight gain after 4 weeks of therapy. The largest response was observed among the severely malnourished children 18 . The reason for this significant improvement was due to provision of adequate food supplement in accordance with national guidelines; prompt referral to the hospital in case of emergency; comprehensive community work.…”
Section: Discussionmentioning
confidence: 91%